Relationship Between Financial Development and Carbon Emissions: Empirical Evidence from Türkiye with Fractional Frequency Fourier Approaches - Havanur Ergün Tatar; Hamza Çeştepe (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractThis study empirically analyzes the relationship between carbon emissions, one of the most important indicators of environmental pollution, and financial development. Using data from Türkiye for the period 1995-2019, the fractional frequency Fourier ADL cointegration method -previously unused in similar studies- is employed for the analysis. The results, which also account for economic growth, demonstrate a cointegration relationship between the variables. Additionally, the FMOLS method is utilized for model estimation, concluding that financial development and growth lead to increased carbon emissions. The study suggests that loans provided to the financial sector should be directed towards technological investments that reduce carbon emissions